Predissociation and pressure dependence in the low frequency far wing of the Wulf absorption band of ozone near 1.2 µm. (September 2021) - Vasilchenko, Semen; Mondelain, Didier; Kassi, Samir; Campargue, Alain
Highlights: The spectrum of ozone is recorded for the first time in the -1 far wing tail of the electronic Wulf band (7920-8700 cm-1). The spectrum includes the 3A2(000)–X(020) and 3A2(000)–X(100) hot bands centered near 8154 and 8450 cm-1, respectively. A detailed line profile study allowed disentangling the predissociation and pressure line broadenings. The life time of 3 A2 (000) upper states is determined from sixty line profiles. Predissociation is linked to the coupling of 3 A2 (000) with highly excited vibrational "doorway" states of the electronic ground state. Abstract: The weak low frequency tail of the ozone Wulf band is newly studied by high sensitivity cavity ring down spectroscopy (CRDS) in the 7920–8700 cm −1 range. Although strongly obscured by impurity lines, the ozone absorption signature shows up in the recorded spectra as two mostly unresolved absorption bands. These two bands with maximum near 8154 and 8450 cm −1 are hot bands from the (020) and (100) ground state vibrational levels reaching the same predissociated 3 A2 (000) upper state of 16 O3 . The observed bands include a mostly structureless continuum and lines exhibiting a clear broadening due to the predissociation of the 3 A2 (000) upper state. On the basis of assignments of the rotational structure available in the literature for the 3 A2 (000)-X 1 A1 (000) cold band centered near 9553 cm −1, seventy-four relatively narrow lines could be rotationally assigned to the 3 A2 (000)-X 1 A1 (020) and 3 A2 (000)-X 1 A1 (100) hot bands. A line shape analysis, performed using a Voigt profile, provided the width of the Lorentzian component. Additional recordings performed at various pressures for 18 lines allowed to disentangle the pressure and predissociation contributions to the fitted Lorentzian widths. As a result, the newly derived pressure broadening coefficients of the considered rovibronic transitions are found to be similar to those of the rovibrational infrared bands. All the lines studied are affected by significant predissociation due the spin-orbit coupling between the 3 A2 (000) level and high lying dissociative vibrational levels of the X 1 A1 electronic ground state. The resulting set of predissociation widths for sixty lines ranges between 9 × 10 −3 and 0.2 cm −1 corresponding to upper state lifetime of 560 and 25 ps, respectively. The reported results are discussed in relation with previous experimental and theoretical studies.